Odložení léčby u pacientů s obsedantně kompulzivní poruchou - Praško, Ján; Cinculová, Andrea; Buliková, Barbora; Adamcová, Katarína; Kopřivová, Jana; Raszka, Michal (Psychiatrie (Praha, Print), 2009)
The stigma of psychiatric disorder is mainly reflected in knowledge about mental illness and attitudes toward people with mental illness. The affected individual may experience devaluation and rejection. Just the psychiatric treatment itself may results in automatic labeling. Therefore patients with obsessive compulsive disorder are afraid of psychi- atric labeling. They often attempt avoiding stigmatization by denying the disorder and delaying or avoiding the treatment. Thus, the labeling itself can be one of the maintaining factors of the disorder. There was 9,57 year of treatment delay in our group of 33 obsessive compulsive patients.
Keywords: delay of treatment; obsessive compulsive disorder; stigmatization